Avaliação do uso de cinzas de carvão mineral como melhorador de adesividade em misturas asfálticas - Xavier, Marioleide de Farias (2016)
The moisture damage cause negative impacts on the asphalt pavement, which may aggravate the defects commonly found in these structures. Contact with moisture may result in degradation of adhesion between the asphalt binder and the aggregates. This work deals with the evaluation of the use of coal ash as adhesivity improvers in asphalt mixtures, using them as mineral filer, and also comparing the mechanical behavior of asphalt mixtures containing mineral coal ash, hydrated lime CH -I typeand stone powder as fíleres. For the development of the present work, were collected fly ashes directly from the process silos and ashes from the storage module of the thermoelectric power plants, totalizing 34 samples. Coal ash collected in the storage module showed a larger grain size than the fly ash. The chemical characterization of the collected material, through diffraction and X-ray fluorescence techniques, showed that the collected material is quite heterogeneous, with 67.7% of the collected ashes belonging to Class C, and the rest of the ashes framed In Class F, according to ASTM C618 / 2015. Regarding the evaluation of tensile strength tests, the use of coal ash in a percentage of 4% by weight of aggregate did not represent an increase in the tensile strength of the mixtures studied, however, when the ash was associated with lime, occurred a increase in stiffness in the studied asphalt mixtures. In the evaluation of moisture damage, through the useof modified Lottman test, it was evident that the use of ashes at a 4% by weight of aggregate presented results similar to those of the natural filler, obtaining values of average ITS below than 50%. On the other hand, the use of ash associated with lime represented an increase in resistance to moisture damage, obtaining an average ofindirect tensile strength greater than 80%. The fact of some ashes belong to Class C or F, or even that some ashes be more alkaline than others, did not reflect significant gains in resistance to moisture damage.